Investigative health and ecological risk assessment of trace elements in pharmaceutical deposition near Dhaka: An endemic industrial surge of Bangladesh - Sharmin Akter Lisa; Sharmeen Nishat; Md. Kamal Hossain; Lokman Hosen; Mohammad Moniruzzaman; Md. Samrat Mohay Menul Islam; M. A. A. Shofi Uddin Sarkar (PLoS ONE, 2026)
The pharmaceutical industry (PMI) is one of the fastest-expanding sectors in Bangladesh. The environment of this country is suffering from pollution done by discharging PMI effluents into the surface water bodies. Twelve trace elements (As, Se, Pb, Be, Cd, Co, Cr, Cu, Mn, Ni, V, and Hg) were analyzed in water and sediment samples collected from nine distinct pharmaceutical outfalls using ICP-MS to monitor contamination from pharmaceutical waste. Pollution levels, associated health, and ecological risks were evaluated using various indicators. The water pollution indices depicted that the associated outfalls’ surface water was less polluted, and the health indices demonstrated that, although the risks were far below the threshold value, prolonged exposure to the metal content of the surface water, particularly Cd, may cause potential health hazards. The simulated probabilistic analysis estimated median carcinogenic risks for both adults and children below the 1 × 10 −4 benchmark. According to Monte Carlo Simulation, about 0.5% of adults and 0.3% of children are at carcinogenic risk. The geoaccumulation index (I geo ), enrichment factor (EF), and contamination factor (CF) values revealed that the study area was moderately contaminated with Cd, while other metal contamination was less prevalent. The potential ecological risk (PER) index revealed that the maximum studied locations were at low to moderate risk, whereas two locations were at considerable risk. Principal component analysis (PCA) reveals that, Se, Ni, and As had comparable environmental characteristics and made the largest contributions to the overall variance for sediment samples, whereas Ni, V, and As had similar environmental characteristics and made the largest contribution to the overall variation for water. Pearson correlation depicted a significant correlation among several elements, suggesting some anthropogenic activities contributed to contamination. Despite being categorized according to the USFDA, the cluster analysis revealed that the examined industries could be classified differently regarding trace elements release.